Feature Extraction o Condition Monitoring Data on Heavy Equipment's Component Using Principal Component Analysis (PCA). (August 2019) - Yudha, M A; Surjandari, I; Zulkarnain
Abstract: The maintenance strategy is significantly important to minimize risk and impact on equipment productivity from component failure. The mechanical transmission on heavy equipment has a function to change speed and torque from engine to final drive. Because of the function that carries high loads which leads to an increase in wear particles, a condition monitoring (CM) approaches is employed. CM data is consisting of 26 parameters and need to reduce the dimension for simplifying correlated variables into fewer independent principal components (PCs). Principal component analysis (PCA) method has been applied to this dataset and deciding 10 PCs with explaining 73.62% variability of the data.